An interventional study to assess knowledge regarding rabies in secondary school students - Sancheti, Poonam Vijay; Mangulikar, Suresh Konappa (International Journal Of Community Medicine And Public Health, 2017)
Background: Despite the tremendous progress in vaccination, rabies is widely prevalent in India. In India, about 15 million people get animal bite, every year and need post-exposure prophylaxis. Although all age groups are susceptible, rabies is most common in children. 40% of post exposure immunization is given to children aged 5-14 years. On this background, present study was designed to assess knowledge regarding rabies in secondary school students and to impart health education to them. Methods:An interventional study was carried out in an English medium secondary school. Total 140 students of age 13-15 years were studied. Baseline knowledge regarding rabies was determined by questionnaire method. A health education intervention regarding rabies was given to them. Knowledge was again tested using same questionnaire after 10 days. The data gathered was analysed using appropriate statistical test. Results: Out of total, 65.71% were male and 34.29% were female students. 85.71% students knew that dog bite can cause rabies.74.28% students knew about antirabies vaccination for human, which rose to 85% after health education. 66.43% students perceived application of turmeric, oil, chuna on wound as beneficial before health education. There was significant difference between knowledge regarding mode of transmission of rabies, animals that transmit rabies in India and immediate steps after animal bite in students before health education intervention. Conclusions:There was inadequate knowledge regarding rabies, in students which shown significant increase after health education.